Gendered Due Process of Juvenile Justice - Annette R. Appell (Washington University Journal of Law & Policy, 2017)
This Essay illustrates how the United States Constitution has developed gendered jurisprudence for children and families that affords children a higher level of due process in juvenile courts than is afforded to their parents. Appell discusses this jurisprudence through the lens of child protection and delinquency cases, followed by the laws treatment of children outside of the familial context. Appell highlights the higher level of constitutional freedom afforded children who break the law versus their parents who raise them and ends with a discussion of the implications this has on juvenile jurisprudence.
Keywords: jurisprudence; gendered jurisprudence; juvenile crime; family; due process; parents; United States Constitution; juvenile courts; child protection; delinquency